2021
DOI: 10.1039/d0ra08586c
|View full text |Cite
|
Sign up to set email alerts
|

Rational construction of free-standing P-doped Fe2O3 nanowire arrays as highly effective electrocatalyst for overall water splitting

Abstract: Designing electrode structures with high activity is very significant for energy conversion systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Testing the HER activity also shows the same pattern (Figure b); the overpotential of the three catalysts was 184, 243, and 291 mV at a current density of 10 mA cm –2 , respectively. Therefore, as shown in Table , ,, these result confirmed the advantage of this MOF intermediate in situ construction strategy and the binder-free electrocatalysis system.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Testing the HER activity also shows the same pattern (Figure b); the overpotential of the three catalysts was 184, 243, and 291 mV at a current density of 10 mA cm –2 , respectively. Therefore, as shown in Table , ,, these result confirmed the advantage of this MOF intermediate in situ construction strategy and the binder-free electrocatalysis system.…”
Section: Resultssupporting
confidence: 73%
“…28−36 Additionally, to further explore the advantage of a designed construction mode of this catalytic system, the MIL-88A/NF precursor was further treated by oxidation instead of being phosphated to obtain the Fe 2 O 3 /NF catalytic system, as it is well-known that iron oxides also have electrocatalytic activity for overall water splitting. 37 The oxides were obtained by calcining MIL-88A/NF directly in air at different temperatures; then their catalytic properties were tested. As shown in Figure S13, the clear diffraction peaks at 44.3, 51.7, and 76.2 can be attributed to the characteristic peaks of metallic nickel, with the other peaks corresponding to the characteristic peaks of Fe 2 O 3 (JCPDS No.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32−34 For instance, Zhang et al 35 demonstrated that the incorporation of a P anion into Fe 3 O 4 could evidently improve its HER catalytic performance. Tong et al 36 successfully doped a P anion into Fe 2 O 3 , which possessed optimized HER performance compared with pristine Fe 2 O 3 . Inspired by these studies, we assumed that the element S, of which the electronegativity and atomic radius are comparable to those of P, could easily be doped into Fe 2 O 3 and also optimize the catalytic activity of Fe 2 O 3 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have displayed that the preparation processes and regulation control strategies of recent research on ferric oxide are seemingly complicated, , and heteroatom doping would be an effective and simple approach to enhance the conductivity and improve the intrinsic activity of transition metal oxide. For instance, Zhang et al demonstrated that the incorporation of a P anion into Fe 3 O 4 could evidently improve its HER catalytic performance. Tong et al successfully doped a P anion into Fe 2 O 3 , which possessed optimized HER performance compared with pristine Fe 2 O 3 . Inspired by these studies, we assumed that the element S, of which the electronegativity and atomic radius are comparable to those of P, could easily be doped into Fe 2 O 3 and also optimize the catalytic activity of Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%